PELAKSANAAN PROGRAM KEGIATAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SD MUHAMMADIYAH 02 SANGATTA - Muhammad Abdul Rozak, Faelasup (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
To help students behave in accordance with Islamic teachings contained in the Qur'an and Hadith, religious character education is an important component in this process. Unfortunately, there are many students who do not follow Islamic principles in the classroom and outside the classroom. The need for religious character education is very important. At SD Muhammadiyah 02 Sangatta, we hope to find out how big the impact of religious habituation is in forming religious character. The data used in this qualitative research did not come from numerical sources, but from official documents used at SD Muhammadiyah 02 Sangatta, such as interview transcripts, field notes, personal letters, memos and other materials. Religious habituation activities carried out every day are an excellent habituation strategy for developing students' religious character before and after studying. Consistent daily religious practice has long-term effects that students can internalize and remember, making it easier for them to practice it even when the teacher is not around.